Ramjet Nozzle Analysis for Transport Aircraft Configuration for Sustained Hypersonic Flight - Raman Baidya; Apostolos Pesyridis; Maxim Cooper (Applied Sciences, 2018)
For the past several decades, research dealing with hypersonic flight regimes has been restricted mainly to military applications. Hypersonic transportation could be a possible and affordable solution to travel in the medium term and there is renewed interest from several private organisations for commercial exploitation in this direction. Various combined cycle propulsion configurations have been proposed and the present paper deals with implications for the nozzle component of a ramjet configuration as part of one such combined cycle propulsion configuration. An investigation was undertaken for a method of turbine-based propulsion which enables the hypersonic vehicle to take off under its own power and propel the aircraft under different mission profiles into ramjet operational Mach regimes. The present study details an optimal method of ramjet exhaust expansion to produce sufficient thrust to propel the vehicle into altitudes and Mach regimes where scramjet operation can be initiated. This aspect includes a Computational Fluid Dynamics (CFD)-based geometric study to determine the optimal configuration to provide the best thrust values. The CFD parametric analysis investigated three candidate nozzles and indicated that the dual bell nozzle design produced the highest thrust values when compared to other nozzle geometries. The altitude adaptation study also validated the effectiveness of the nozzle thrust at various altitudes without compromising its thrust-producing capabilities. Computational data were validated against published experimental data, which indicated that the computed values correlated well with the experimental data.